Development Of Digitalization In Goods Transportation Services ( Trucking ) Companies To Support Strategies To Increase Competition Competitiveness & Satisfaction Customer - Setyawati, Aswanti; Dudi Firmansyah (Dinasti International Journal of Digital Business Management, 2024)
The effect of development of digitalization in companies providing goods transportation services (trucking) on supporting strategies to increase competitiveness and customer satisfaction is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the development of digitalization in companies providing goods transportation services (trucking) influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) development of digitalization in companies providing goods transportation services (trucking has an effect on supporting strategies to increase competitiveness; 2) has an effect on y1; and 2) development of digitalization in companies providing goods transportation services (trucking) has an effect on customer satisfaction.